Modern technologies in the work of Music Collection Department - Osowski, Mirosław (Biblioteka Uniwersytecka we Wrocławiu, 2015)
The article presents the applicability of modern technologies in the work of Music Collection Department and their influence on the Department's working methods and servicing the users. Presented is a long-years collaboration with RISM Catalog within the scope of music manuscripts processing in Kallisto program, the specificity of cataloging new music prints in MARC21 format in Wrocław University Library electronic catalog and in NUKAT catalog as well as description in Dublin Core and full text presentation of historical music materials in Digital Library of University of Wrocław. A closer look is taken at rendering available for the Library users detailed information about music document resources via digitization and access to digitized card catalogs at Wrocław University Library homepage. Moreover, the Department employees' participation in numerous projects is discussed in which various computer techniques as well as information and communication technologies are applied.
Keywords: music documents; Music Collection Department; catalogs; digitization; computerization